PERSEPSI MASYARAKAT TERHADAP PEMBULATAN HARGA PADA TRANSAKSI JUAL BELI MENURUT SYARIAT ISLAM DI MINI MARKET INDOMARET KELURAHAN PONTAP KOTA PALOPO - .... ...... (Program Studi Perbankan Syariah, IAIN Palopo, 2020)
Abstract: The main problems in this research are (1) public perception of price rounding in buying and selling transactions at Indomaret minimarkets; (2) Islam's view about replacing the remaining purchase money with sweets at Indomaret minimarket. In this study the authors used a type of field research, the design used was qualitative research that is research producing data in the form of written or oral words from people who could be observed. This research raises facts. There are two data sources that researchers use, namely primary data sources and secondary data sources. The primary data source is data directly taken from the object of the researcher, namely the Indomaret cashier and the customer. The primary data source is derived from field data obtained from observations and interviews. Secondary data sources are data taken in the form of Indomaret documents. The results of the study showed that most people accepted price rounding on the grounds that they were accustomed but there were still a small number of people who felt dissatisfied and disagreed if the price rounding practice was carried out. If in the fulfillment of the remaining money of this purchase there is a buyer who feels less willing, he can choose to keep abreast of what the seller says or cancel the sale and purchase. The Islamic view of replacing the rest of the money with candy is allowed to see the scarcity of small change so that the manager of Indomaret provides candy instead. This gave rise to the rule of one rule which reads